Severe Mycoplasma bovis outbreak in an Austrian dairy herd. (November 2015) - Pothmann, Harald; Spergser, Joachim; Elmer, Josef; Prunner, Isabella; Iwersen, Michael; Klein-Jöbstl, Daniela; Drillich, Marc
A conventional dairy farm, housing 19 Austrian Simmental cows, experienced a spontaneous outbreak of a Mycoplasma bovis infection, showing severe clinical signs of respiratory tract disease, clinical mastitis, and tremendous drop in milk production. Despite intensive therapy, 5 cows died within 2 weeks or were euthanized. From the remaining cows, bacteriological culture and polymerase chain reaction revealed M. bovis in 10 of 14 milk samples. Mycoplasma bovis was found in 1 of 5 randomly collected nasal swabs. Autopsy of 1 cow revealed infection of the lungs and the udder with M. bovis. The 13 M. bovis isolates from milk samples, nasal swabs, lungs, and udder were genotyped by multilocus variable number of tandem-repeat analysis, and indicated that described infections were caused by a single M. bovis strain. The virulent M. bovis strain resulted in dramatic economic loss to the farmer. To control the disease, culling of all animals, including heifers and calves, was recommended, and strict hygienic measures were implemented before introducing new animals to the farm.